Medicinal importance of Kaempferia galanga L. (Zingiberaceae): A comprehensive review - Aswin Rafif Khairullah; Tridiganita Intan Solikhah; Arif Nur Muhammad Ansori; Ristag Hamida Hanisia; Gavrila Amadea Puspitarani; Amaq Fadholly; Sancaka Cashyer Ramandinianto (Shahrekord University of Medical Sciences, 2021)
Kaempferia galanga included in the Zingiberaceae family is one of the potential medicinal plants with aromatic rhizome. In traditional medicine in Asian countries, this plant is widely used by local practitioners. This plant is widely cultivated in most Southeast Asian countries such as Cambodia, Vietnam, Malaysia, Thailand, and Indonesia. Ethyl-para-methoxycinnamate and ethyl-cinnamate are found as the main compounds in hexane, dichloromethane, and methanol extracts of K. galanga. This plant is traditionally used as an expectorant, stimulant, diuretic, carminative, and antipyretic remedy. In addition, K. galanga is used for treatment of diabetes, hypertension, cough, asthma, joint fractures, rheumatism, urticaria, vertigo, and intestinal injuries. Therefore, this study aimed to give a sneak peek view on galangal's ethnobotany, toxicology, pharmacology, and phytochemistry.